Active vibration control of a flexible beam structure using chaotic fractal search algorithm - Tuan Abdul Rahman, Tuan Ahmad Zahidi; As'arry, Azizan; Abdul Jalil, Nawal Aswan (Elsevier, 2017)
The performance of lightweight and flexible systems such as beam, plate and shell structures are vulnerable to excessive vibration level. Thus, many vibration control techniques have been developed in the past two decades in order to overcome this problem. In this paper, the development of active vibration control to suppress the unwanted vibration from a flexible beam structure is presented. The objective of this work was to evaluate the performance of chaos-enhanced Stochastic Fractal Search (CFS) optimization algorithm in modeling and vibration control of flexible beam system. Parametric modeling of the system was developed using auto-regressive exogenous (ARX) model structure based on the input-output data from previous experimental finding. The first two resonance frequencies of flexible beam structure was found at 3.418 Hz and 21 Hz. The accuracy of generated flexible beam model was validated using correlation and system stability tests. A PID controller incorporated with CFS optimization algorithm was employed to attenuate the unwanted vibration from the flexible beam system. Based on the proposed method, about 83.95% of the initial vibration disturbance successfully been suppressed with the mean-squared error value of 1.5178 x 10-4 been achieved. In conclusion, the simulation study indicates that the CFS algorithm possess capability to extract an adequate and stable model of the flexible beam structure, hence a better performance of control strategy can be achieved.